ADAPTASI MUALAF TIONGHOA DAN KELUARGANYA DI KOTA PEKANBARU - Dyah Ayu Ernawati; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
A person who is of Tinghoa ethnicity with his old religion decided to become a convert, this difference has an impact on the interaction of Chinese converts with his family which results in being ostracized by his family, even expelled and no longer considered a member of his family, but not a few of the informants whose decisions are acceptable by family and coexist in these differences. This study interviewed 5 (five) key informants who are Chinese converts, this discussion examines the interaction of informants and how to adapt converts to their families who have different beliefs and even rules in living life, this discussion discusses strategies that converts were carried out in overcoming these differences, in this case the researcher used the Merton anomie typology namely the typology of Ritualism and the typology of Retreatism. Furthermore, this study also uses the Triangulation method, in which the researcher also interviews the families of converts as supporting informants to further prove the accuracy of the data. This phenomenon attracts researchers to raise the title of the study